Preconception micronutrient supplementation positively affects offspring cognition at 10–11 years of age: A randomized controlled trial in Vietnam - Nguyen, Phuong Hong; Tran, Lan M.; Khuong, Long Q.; Nguyen, Phuong T.; Nguyen, Bac V.; Be, Thanh H.; Young, Melissa F.; DiGirolamo, Ann M.; Martorell, Reynaldo; Ramakrishnan, Usha (Elsevier, 2024)
Objectives: The importance of maternal periconceptional nutrition for offspring health and development has received increased attention recently, yet very few intervention studies have evaluated the long-term effects on offspring growth and cognitive outcomes. We evaluated the impact of preconception weekly multiple micronutrients (MM) or iron and folic acid (IFA) supplementation compared to folic acid (FA) alone on offspring body composition and cognitive function during the school-age years and early adolescence.